2015
DOI: 10.4274/tjod.32767
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy with sigmoid volvulus: A case report with literature review

Abstract: Sigmoid volvulus refers to torsion of a segment of the alimentary tract, which often leads to bowel obstruction and ischemic changes. Sigmoid volvulus is an acute surgical emergency because delay in diagnosis and management can cause adverse maternal and fetal complications. Sigmoid volvulus typically presents with acute-on-chronic abdominal distension that may develop slowly over 3-4 days. An early and effective resuscitation with fluid replacement, electrolyte balance correction, prophylactic antibiotics and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…The overall study concluded that to reduce the number surgical site infection and prevent the risk factors it is necessary to maintain aseptic surgeries, implement infection prevention practices and give antibiotic prophylaxis to reduce morbidity in women undergoing caesarean section. 4 Farret, Dalle, Monteiro, Wurdig Riche, & Antonello (2015) conducted a retrospective case-control observational study that was conducted in Femina hospital in Porto Alegre, Brazil to determine the risk factors and impact of antibiotic prophylaxis for surgical site infection on caesarean section. A total number of 8180 caesarean section records were reviewed and 118 (1.44%) were diagnosed as having surgical site infection.…”
mentioning
confidence: 99%
“…The overall study concluded that to reduce the number surgical site infection and prevent the risk factors it is necessary to maintain aseptic surgeries, implement infection prevention practices and give antibiotic prophylaxis to reduce morbidity in women undergoing caesarean section. 4 Farret, Dalle, Monteiro, Wurdig Riche, & Antonello (2015) conducted a retrospective case-control observational study that was conducted in Femina hospital in Porto Alegre, Brazil to determine the risk factors and impact of antibiotic prophylaxis for surgical site infection on caesarean section. A total number of 8180 caesarean section records were reviewed and 118 (1.44%) were diagnosed as having surgical site infection.…”
mentioning
confidence: 99%
“…It depends on the gestational age, the viability of the fetus, and the degree of intestinal necrosis. In the absence of peritoneal signs or mucosal ischemia, a detorsion and decompression via sigmoidoscopic placement of a soft rectal tube are a reasonable approach 9 . However, it seems that during the third trimester, colonoscopic detorsion is less successful among pregnant women compared to the rest of the patients.…”
Section: Discussionmentioning
confidence: 99%
“…In pregnant patients, endoscopic decompression can be difficult to achieve due to progressive uterine enlargement. 13 Successful multiple endoscopic interventions during pregnancy have been reported and are becoming the preferred method to relieve obstruction but are still very uncommon since less than 10 cases of recurrent SV in the same pregnancy have been des cribed. 3,4,11,14,15 In the absence of acute perforation or ischemia, definitive operative treatment with elective colon resection with primary anastomosis is recommended after resolution of the acute volvulus phase to prevent recurrence.…”
Section: Discussionmentioning
confidence: 99%